Centrosome Polarization in T Cells: A Task for Formins - Andrés-Delgado, Laura; Antón, Olga M.; Alonso, Miguel A. (Frontiers in Immunology, 2013)
T-cell antigen receptor (TCR) engagement triggers the rapid reorientation of the centrosome, which is associated with the secretory machinery, towards the immunological synapse (IS) for polarized protein trafficking. Recent evidence indicates that upon TCR triggering the INF2 formin, together with the formins DIA1 and FMNL1, promotes the formation of a specialized array of stable detyrosinated MTs that breaks the symmetrical organization of the T-cell microtubule (MT) cytoskeleton. The detyrosinated MT array and TCR-induced tyrosine phosphorylation should coincide for centrosome polarization. We propose that the pushing forces produced by the detyrosinated MT array, which modify the position of the centrosome, in concert with Src kinase dependent TCR signaling, which provide the reference frame with respect to which the centrosome reorients, result in the repositioning of the centrosome to the IS.